Horizontal axis Magnus wind turbine performance according to their geometric and kinematic variables - Richmond-Navarro, Gustavo (2016)
This study covers the analysis of a horizontal axis wind turbine that uses rotating cylinders instead of blades. The working principle of this wind generator is the Magnus effect, which happens when the cylinders start rotating, giving rise to an interaction between the incident wind and the air dragged by the walls of the moving cylinders. This generates lift which puts the turbine in motion. The goal of this investigation was to characterize this type of turbine by means of numerical and mathematics methods that permit determination of the power vs wind speed curve’s behaviour as a function of working parameters of Magnus horizontal axis wind turbines. In order to study turbines performance, a non-iterative method is proposed and implemented in code. This approach allows the prediction of the output power, which is validated by experimental measurements of conventional turbines. The method was adapted to Magnus turbines. It was used to obtain the power curve behavior given geometry variations including changes in the number of rods, as well as turbine and cylindrical blade’s angular velocities.